2014
DOI: 10.1007/s10482-014-0308-z
|View full text |Cite
|
Sign up to set email alerts
|

An acidothermophilic functionally active novel GH12 family endoglucanase from Aspergillus niger HO: purification, characterization and molecular interaction studies

Abstract: Endoglucanase (EG) from Aspergillus niger HO was sequentially purified through ultrafiltration, ion exchange and size exclusion chromatography to homogeneity, with an overall recovery of 18 %. The purified EG was a monomeric protein with a molecular weight of about 55 kDa. The enzyme was optimally active at pH 3.5 and 70 °C with a half life (t1/2) of 3 h and Km value of 2.5 mg/ml. Metal ions, such as Ca(2+) and Co(2+) helped in enzyme induction, while Hg(2+) and Cu(2+) strongly inhibited the enzyme activity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Several reports have indicated that Co 2+ can enhance the activity of endoglucanases from E. coli Rosetta 2 and Aspergillus niger (Rawat et al, 2015; Martin et al, 2014). In the present study, the activity of EglC22b was also increased by the presence of Co 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have indicated that Co 2+ can enhance the activity of endoglucanases from E. coli Rosetta 2 and Aspergillus niger (Rawat et al, 2015; Martin et al, 2014). In the present study, the activity of EglC22b was also increased by the presence of Co 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Of these, endo-␤-1,4-glucanase plays a key role in cellulose degradation, as it can randomly break down the cellulose backbone internally to release free chain ends. According to the classification of carbohydrate enzymes (http://www.cazy.org/), endo-␤-1,4-glucanases are often found in GH families 6,7,8,9,12,44,45,48,51,74, and 126 (5). Among them, GH12 is a unique group possessing both endoglucanase and xyloglucanase activities (6), and GH12 endoglucanases usually attract attention due to their higher endo-␤-1,3-1,4-glucanase activity.…”
Section: Importancementioning
confidence: 99%
“…A large number of fungal endoglucanases of GH12 have been cloned and extensively studied, including the EGIII from Trichoderma reesei (8), a thermostable Cel12A from Humicola grisea (4), and the highly active EG from Aspergillus niger (9). Of the eight structure-resolved fungal endoglucanases of GH12, two catalytic sites, Glu116 and Glu200, and eight substrate binding sites, Trp7, Trp22, Val57, Tyr111, Ile130, Asn151, Met154, and Phe202 (EGIII numbering), are highly conserved (8).…”
Section: Importancementioning
confidence: 99%
“…36,37 Metal ions can cause either inhibition of enzyme or activation, based on the nature of the cations. 36 Determining the effect of metal ions on enzyme hydrolysis is important because many industrial applications require their addition at various stages of the process, and the greater part of the enzymes requires a specific metal ion as a cofactor for their catalytic activity. 36,38 Experiments were conducted in the activity method described above with different concentrations of various salt ions.…”
Section: Effects Of Some Metal Ions On Hydrolysismentioning
confidence: 99%
“…36 Determining the effect of metal ions on enzyme hydrolysis is important because many industrial applications require their addition at various stages of the process, and the greater part of the enzymes requires a specific metal ion as a cofactor for their catalytic activity. 36,38 Experiments were conducted in the activity method described above with different concentrations of various salt ions. Effects of the metal ions on the enzyme activity for hydrolysis of CMC are shown in Table 3.…”
Section: Effects Of Some Metal Ions On Hydrolysismentioning
confidence: 99%